PENGARUH SUPERVISI MANEJERIAL DAN MOTIVASI KERJA TERHADAP KINERJA KEPALA SEKOLAH PADA SEKOLAH DASAR NEGERI MENURUT PERSEPSI GURU SE-KOTA PADANG PANJANG - Erichyat Putra (IAIN Batusangkar, 2018)
The background of the research was the poor performance of the elementary school headmasters so that their main tasks and functions had not been fulfilled yet. It was researched based on elementary schools teachers’ perceptions in Padang Panjang. The purpose of this research was to find out the influence of schools headmasters’ managerial supervision and working motivations towards their performance. The results of the research found that: (1) the schools Headmasters’ managerial supervisions had positive and significant influence towards their professionalism, namely 17.70 %; (2) their working motivations had positive and significant influence on their professionalism namely 14.40%; and (3) their managerial supervision (X1) and working motivation (X2) had positive and significant influences towards the Headmasters’ performances, namely 39.50%.